Human mobility and human health - Newman, Peter; Matan, Annie (Elsevier, 2012)
Motor vehicles have become the dominant form of transport, but this has had a number of negative human health outcomes. While public health originally drove the need to reduce densities, the latest research now favours the move to more compact cities where active transport can be improved as a transport option. The benefits for healthy transportation choices, economic value and social health are outlined.